Edukasi Pendidikan Keputihan Pada Remaja Putri - Mega Ade Nugrahmi; Mariyona, Kartika; Sari, Amelya Permata; Rusdi, Pagdya Haninda Nusantri; Yanti, Rifni Seppri (Universitas Pahlawan Tuanku Tambusai, 2024)
Fungi can breed in areas or countries with tropical climates and cause many cases of vaginal discharge in women. In Indonesia, the incidence of vaginal discharge continues to increase every year, reaching 70%. In Bukittinggi Agam, there is a rate of vaginal discharge that occurs in teenage girls, namely 71.7%. Many teenagers who experience vaginal discharge do not know about this problem. The aim of this community service is to find out vaginal discharge in young women related to personal hygiene. The sample consisted of young women in Alley Pine Aur Kuning, Bukittinggi city. The results of this community service show that health education related to vaginal discharge for young women can have a positive impact regarding the personal hygiene of these teenagers which can be seen from before and after the education is carried out to teenagers. The conclusion shows that education regarding vaginal discharge is very necessary for young women, so that they can maintain personal hygiene of teenagers to prevent symptoms of cervical cancer.